2017
DOI: 10.1001/jamaoto.2016.4238
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal to Redefine Close Surgical Margins in Squamous Cell Carcinoma of the Oral Tongue

Abstract: IMPORTANCE Resection of the primary tumor with negative margins is the gold standard treatment for squamous cell carcinoma of the oral tongue (SCCOT). A microscopically positive surgical margin is clearly associated with a higher risk for local recurrence, whereas a negative margin has traditionally been defined as greater than 5.0 mm clearance from the tumor, with lesser margins arbitrarily designated as close. The precise cutoff at which the risk for local recurrence with a close margin approximates that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 24 publications
(41 reference statements)
1
94
1
1
Order By: Relevance
“…Although patients with T1‐2N0M0 OCSCC can be treated with surgery alone, those with positive and close margins may benefit from adjunctive treatment . It has been suggested that adequate resection of OCSCC requires at least 5‐mm margins, although smaller margins have also been suggested . Because of the complexity of these tumors, clear margins are achieved in only 50% to 80% of patients treated at cancer centers .…”
Section: Introductionmentioning
confidence: 99%
“…Although patients with T1‐2N0M0 OCSCC can be treated with surgery alone, those with positive and close margins may benefit from adjunctive treatment . It has been suggested that adequate resection of OCSCC requires at least 5‐mm margins, although smaller margins have also been suggested . Because of the complexity of these tumors, clear margins are achieved in only 50% to 80% of patients treated at cancer centers .…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies provided a more objective definition of ECS and margin status, in order to improve identification of high-risk HNSCC. 8,29 Recent inclusion of one of the parameters into the TNM staging system may help to guide the intensification of treatment for high-risk HNSCC. …”
Section: Resultsmentioning
confidence: 99%
“…8,29 These studies empirically quantified ECS extent and margin status by two-dimensional metric measurements, before subjecting it to rigorous statistical analysis. Time-dependent receiver operator characteristic (ROC) analysis was chosen to identify a prognostic cut-off at which sensitivity and false-positive rate were balanced optimally for both individual parameters.…”
Section: Recent Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Recently, the definition of a negative margin was proposed to 2.2 mm, decreasing from the previous standard of 5 mm for the oral tongue. 3 Another study found cuts within 1 mm of oral cavity SCCa tumor margins are associated with significantly increased recurrence rates. 4 Additionally, the incidence rate for differentiated thyroid carcinomas in the United States is approximately 20 per 100,000 females and 6 per 100,000 males, predominantly papillary and follicular carcinoma.…”
Section: Introductionmentioning
confidence: 99%